VD_FINDINFO Arrêt / 2025 / 675 vom 12. August 2025 - VD Tribunal cantonal (2025)
DROIT D'OBTENIR UNE DÉCISION, PROCÈS DEVENU SANS OBJET, RADIATION DU RÔLE | 29 al. 1 Cst., 56 al. 2 LPGA, 94 al. 1 let. c LPA-VD